Examining Lifestyle Behaviours and Weight Status of Primary Schoolchildren: Using Mozambique to Explore the Data Gaps in Low- and Middle-Income Countries - Manyanga, Taru (Université d'Ottawa / University of Ottawa, 2019)
The emergency of malnutrition, in all of its forms, and physical inactivity among children and adolescents as serious public health challenges, especially in resource-limited low- and middle-income countries is concerning and requires attention. Data on the prevalence of unhealthy weight status and levels of physical inactivity among children and adolescents in these low- and middle-income countries are limited, not systematically collected nor are they well documented. Accurate prevalence estimates, and an informed understanding of the relationships among movement behaviours and weight status of children and adolescents, are required to facilitate evidence-informed interventions and public health policies in these countries. The main purposes of this dissertation were to examine relationships between lifestyle behaviours and weight status among primary schoolchildren in Mozambique; compare body mass indices and movement behaviours of Mozambican schoolchildren to those of children from other countries; and use these findings to highlight important data gaps that exist in low- and middle-income countries. First, the Active Healthy Kids Global Alliance’s Report Card development methodology was used to conduct thorough narrative literature searches, identify data gaps and research needs which subsequently informed research questions and primary data collection. A published protocol that was developed for the multinational cross-sectional International Study of Childhood Obesity, Lifestyle and the Environment was adopted and used for primary data collection among urban and rural schoolchildren in Mozambique (n=683), to facilitate data comparability. Anthropometric (weight, height, percent body fat, bioelectric impedance, mid-upper-arm circumference, waist-circumference) and accelerometry (nocturnal sleep, sedentary time, various intensities of physical activity) data were objectively measured by trained personnel. Data about lifestyle behaviours (diet and movement behaviours), demographics and environmental (home, neighbourhood, school) factors associated with child weight status were collected using context-adapted questionnaires. As part of this dissertation, six manuscripts were developed and submitted for publication in peer-reviewed scientific journals. Overall, the narrative literature searches revealed a dearth of information about prevalences of unhealthy weight status, and key lifestyle behaviours among children and adolescents in low- and middle-income countries. Results from data collected in Mozambique showed overweight/obesity to be an emerging public health concern, especially among urban children (11.4%), while thinness still persists and is more prevalent among rural schoolchildren (6.3%). Moderate- to vigorous-intensity physical activity, active transport and mother’s body mass index were found to be important modifiable correlates of weight status for Mozambican children. Distinct differences in the prevalences and correlates of lifestyle behaviours (sleep and physical activity) were observed between urban and rural children in Mozambique. The findings showed that mean moderate- to vigorous-intensity physical activity was lower (82.9±29.5 minutes/day) among urban compared to rural Mozambican children (96.7±31.8 minutes/day). Compared to children from 12 other countries, on average, children from Mozambique had lower body mass indices, higher daily moderate- to vigorous-intensity physical activity, lower daily sedentary time and comparable sleep duration. For example, rural Mozambican children had lower mean BMI z-scores (-0.5±0.9) than the rest of the sample (0.4±1.3), 46 more minutes of daily moderate- to vigorous-intensity physical activity, and 99 less minutes of daily sedentary time than the other children. Furthermore, linear distributions of study site-specific body mass index (positive), minutes of daily moderate- to vigorous-intensity physical activity (negative), and daily sedentary time (positive) by country human development index were observed. Compared to others, children from the urban Mozambican site closely resembled those from Nairobi Kenya on body mass index and movement behaviours, whereas those from rural Mozambique were distinctly different from the rest of the sample on many indicators. Findings from this dissertation highlight the importance of including participants from low, medium, high, and very high-income countries in multinational studies investigating contextual and environmental factors related to childhood weight status. The findings revealed important differences between urban and rural children supporting the need to include both in study samples and especially in low- and middle-income countries where the majority of people live in rural areas. Finally, findings from this dissertation have demonstrated that despite the reported global progress in the availability of data about obesity and related factors among children and adolescents, gaps still exist and need to be filled in low- and middle-income countries.
Keywords: Weight status; Children; Physical activity; Sedentary time; Sleep; Diet; Data gaps; Low- and Middle-Income Countries